Hypoinnervation is an early event in experimental myocardial remodelling induced by pressure overload. Issue 6 (9th April 2013) - Mühlfeld, Christian; Schipke, Julia; Schmidt, Albrecht; Post, Heiner; Pieske, Burkert; Sedej, Simon
Abstract Structural and functional remodelling of cardiomyocytes, capillaries and cardiac innervation occurs in left ventricular hypertrophy (LVH) and heart failure (HF) in response to pressure‐induced overload. However, the onset, time course and the extent of these morphological alterations remain controversial. In the present study, we tested the hypothesis that the progression from hypertrophy to HF is accompanied by changes in the innervation (hyper‐ or hypoinnervation). Left ventricles of wild‐type murine hearts subjected to pressure overload‐induced hypertrophy by transverse aortic constriction (TAC) were investigated by morphometric and design‐based stereological methods at 1 and 4 weeks after TAC and compared with sham‐operated mice. Mice developed compensated LVH at 1 week and typical signs of HF, such as left ventricular dilation, reduced ejection fraction and increased relative lung weight at 4 weeks post‐TAC. At the (sub‐)cellular level, cardiomyocyte myofibrillar and mitochondrial volume increased progressively in response to mechanical overload. The total length of capillaries was not significantly increased after TAC, indicating a misrelationship between the cardiomyocyte and the capillary compartment. The myocardial innervation decreased already during the development of LVH and did not significantly decrease further during the progression to HF. In conclusion, our study suggests that early loss of myocardial innervation density and increased heterogeneity occur during pressure overload‐induced hypertrophy, and that these changes appear to be independent of cardiomyocyte and capillary remodelling.